Development of ETNOCHEM Application for Chemistry Learning with STEAM-2C Approach based on Local Wisdom - Nareswari, Tsalis Jauza; Alfaruq, Muhammad Syiham; Laili, Nurul; Anggraini, Lutfia; Putri, Vanesa Kusuma; Setiawan, Nur Candra Eka (Universitas Al Azhar Indonesia, 2024)
Chemical substances containing complex and abstract concepts make it difficult for students to understand, while the existing teaching media have not been able to be a solution for them until now. The development of technology in the digital era is very rapidly affecting various fields including education, which plays an important role in producing quality human resources with the use of technology, one of which is mobile application. The application of mobile application intended for teachers and students in studying chemistry should be designed in accordance with the needs so that learning can take place, so that the ETNOCHEM application is made. The research method used is qualitative with the development using the System Development Life Cycle (SDLC) method that uses the Waterfall model. The development is carried out with the aim that previously abstract and difficult to understand chemicals can be solved using a combination of graphic objects, audio, visual interesting materials, through projects that will be applied by students. The delivery of the material in it uses the STEAM-2C approach to lift various disciplines and is able to connect local wisdom with science.Keywords— chemistry, Mobile, Education, SLDC, STEAM-2C